Educação e espiritualidade : um estudo de caso ressignificando lideranças - Sozo, Martha Luci Maria (2014)
This thesis, Education and Spirituality one case study re-signifying the leads, concepts and reveals in the readings and in the find out of the praxis, an alternative that leads to the thinking and the building of a paradigm which attends XXI Century necessities of humanization. In the trilogy that is conjugated, it is presented, without established importance order, the concepts and meanings that the education has to society. In the emergency to find meanings to our lifetime, the study let to perceive in the literature and in the daily search, a way that proposes a living for the completeness, a meeting with the human being spirituality and spiritual intelligence recognition, no attached to a belief or religion. The education school and in the society, an anchorage in which it may be founded the engagement of the human being that desires the meeting with the constant knowledge search and with the spiritual evolution. At this thinking line and conviction, the research proposes a re-signifying to the leaders characteristics and functions as subjects that inspire wise virtues by means of the conduct and the acquaintance with their collaborators, inspired by the meditation practice. The methodological approach was a simple case study, of qualitative feature, which studies the phenomenon at the place in which it occurs, ONG Brahma Kumaris, internationally respected by its courses and projects, that personifies, with its practice, hope and certainty, the building of a more pacific world, contributing to the formation of leaders that are ready to work for the most emergent causes of this third millennium. The instrument used for this research was the participation of the researcher in Meditation Raja Yoga Course and an interview with this ONG coordinator and teachers that minister the referred course, having as emergent categories: Reasons and Meanings in the BK teachers life , Philosophy and Values of the BK founded by Meditation and Experiences and Expectations in the Lead Exercise, building with the basic orientations of the authors Jager, Cambi and Libaneo for Education, Zohar, Solomon and Wilber for Spirituality and Robinson, Lück and Gilley for lead. Such results let to construct the thesis of that is emergent and possible the interlace between Education and Spirituality having as alternative the meditation Raja Yoga exercise in the practice of a lead that conduct to the re-signification of our lifetime in the search of the Human Being completeness.